The Impact of Carcinogenic Risk Exposure on Housing Values: Estimates from Chemical Reclassifications - van Binsbergen, Jules; Cocco, João F; Grotteria, Marco; Naaraayanan, S Lakshmi (Review of Financial Studies, 2026)
Abstract We quantify the impact of perceived cancer risk on housing values using widely advertised national reclassifications of chemical carcinogenicity in the United States. Combining these information events with an empirical design that compares changes in house values closer to affected toxic plants against those farther away isolates the effect of cancer risk news from other local factors. Focusing on plants previously emitting reclassified carcinogenic chemicals, we estimate a 1–2% decline in housing values within a 3-mile radius compared to those located farther away. The effects are stronger in areas with higher media presence underscoring the role of salience as a mechanism.